General Practice/Family Medicine Portuguese doctors: "technicists" or "systemics"? - Santiago, Luiz Miguel (2022)
To study if the consultation's problems classification of a fictitious case by General and Family Medicine doctors, showed the characteristics of being a mechanistic or a systemic approach. Exploratory cross-sectional observational study in a convenience sample of the General Practice/Family Medicine population, internees included, in April 2020, applying a modified real world clinical case. Central Portugal and the Autonomous Region of Azores. General Practice/Family Medicine specialists and internees. Electronic Doctors invitation to participate, anonymously, in specific doctor's social networks. A self-fulfilling questionnaire was used to verify the classification of a clinical case in Subjective, Assessment and Plan (from the SOAP methodology) with the response options of the International Classification of Primary Health Care (ICPC2) in chapters P (Psychological) and Z (Social) possible for this case. "Technicists" doctors, only classifying "P" codes and "Systemics" classifying "P+Z" or only "Z" ICPC2 codes were defined. Differences between genders, work place, being an internee or specialist and being a tutor in specialized formation were studied. A sample of 227 30% (n=68) males, specialists represented 66% (n=149), of whom 49% (n=73) were internee's tutors and 34% (n=78) were internees, was studied. In the Subjective chapter of the SOAP methodology, 44.1% (n=100) were "technicists", for Assessment n=93 (40.8%) were "technicists" and for P chapter classification 56.8% were "technicists". For S, A and P chapters classification there was no significant difference between the considered variables. In this sample General Practice/Family Medicine Portuguese doctors were more "systemic" for the S and A chapters of the SOAP model, And "technicists" in the P chapter.